Genetic Characterisation of Buffaloes in Kerala Using Cytogenetic Technique - Anilkumar K (Department Of Animal Breeding And Genetics, College Of Veterinary And Animal Sciences, 1991)
Buffaloes from four districts of Kerala formed the materials for this study. Blood samples were collected from external jugular/ear vein, in heparinised tubes. The technique employed was peripheral leukocyte culture technique. Out of the three different mitogens viz., pokeweed mitogen (PWM), phytohemaggultinin (PHA). and a mixture of these two. the mixture of PWM and PHA was found superior in inducing mitosis. A significant interaction between the mitogens and time of addition of mitotic arrester into the medium was observed. The mixture of PWM and PHA at an incubation time of 71 hours was found to produce best results in culture of buffalo lymphocytes followed by PWM at 70 hours. Ideal concentration of colcemid as mitotic arrester in this study was found to be 2 µg and 3 µg per ml of culture media, when the time of action of colcemid was retained for one hour.